Aspects of word-formation in the analysis of the concept LIBERTY - Ляхова, Оксана Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The paper analyses word-formative properties of the concept LIBERTY as a complex mental formation and an important element of Ukrainian language picture of the world. The paper presents the formative aspect of the research: the research of derivational cluster and paradigms may give the idea of semantic and potential of the concept LIBERTY, allows to trace semantic and derivational relationships between the components of word-formative cluster.